Experimental demonstration of a downlink remote optical local oscillator forradio over fiber system - Nik Mohamed, Nik Abdullah (2013)
A downlink remote optical local oscillator for radio over fiber (RoF-ROLO) system was successfully demonstrated experimentally at up-conversion frequency of 12.92 GHz. Up-conversion architecture was employed at the base station (BS) while the optical signal was generated at the central station (CS) using stimulated Brillouin scattering (SBS) technique at frequency of 10 GHz with 25 km of SBS fiber loop length. The optically generated signal was deployed as a remote local oscillator (LO) signal of a mixer at the BS. RoF-ROLO system was specifically designed to achieve the key specifications which are lower input power level, high system conversion gain as well as minimizing the dispersion effect. In this study, about -9.22 dB and -6.99 dB of the system conversion gain have been obtained through the simulation and experimental demonstration respectively at optical carrier input power of 1 dBm.